Molecular modeling, synthesis and biological evaluation of caffeic acid based Dihydrofolate reductase inhibitors - Renu Sehrawat; Ritu Pasrija; Priyanka Rathee; Deepika Kumari; Anurag Khatkar (BMC Chemistry)
Abstract Dihydrofolate reductase (DHFR) is an enzyme that plays a crucial role in folate metabolism, which is essential for cell growth and division. DHFR has been identified as a molecular target for numerous diseases due to its significance in various biological processes. DHFR inhibitors can disrupt folate metabolism by inhibiting DHFR, leading to the inhibition of cell growth. So, a series of caffeic acid derivatives were designed, synthesized, characterized and evaluated for their in vitro ability to inhibit DHFR, as well as their antimicrobial and anticancer properties. Among all synthesized compounds, compound CE11 exhibited the highest DHFR inhibitory activity, with an IC50 value of 0.048 µM, which is approximately four times more potent than methotrexate. Compound CE11 exhibited similar docking performance to methotrexate, binding to the same site and engaging key residues such as Glh30, Phe31, Phe34, and Ser59. It also fit snugly in the hydrophobic pocket of modeled protein. Moreover, substantial hydrophobic interactions were noted between the ligand and the hydrophobic amino acid residues of DHFR. This effectively secured the derivative within the restricted substrate cavity. Furthermore, compound CE11 demonstrated a significant anticancer activity against MCF-7 breast cancer cell line, with an IC50 value of 5.37 ± 0.16 µM. Compounds CE3 and CE15 displayed better antibacterial activity compared to trimethoprim and comparable to ampicillin against the gram-positive bacteria S. aureus. Moreover, compounds CE3 and CE15 have shown better antibacterial activity than standard trimethoprim, ampicillin and tetracycline against the gram-negative bacteria, particularly P. aeruginosa and E. coli. Molecular docking analysis of CE3 revealed that it firmly entrapped into the active site of enzyme through hydrophobic interaction with hydrophobic residues. Additionally, it forms hydrogen bonds with important amino acid residues Ala7, Asn18, and Thr121 with excellent docking score and binding energy (-9.9, -71.77 kcal/mol). These interactions might be contributed to the significant DHFR inhibition and antimicrobial activity. The generated model holds potential value in facilitating the development of a novel category of DHFR inhibitors as anticancer and antimicrobial agents.